Blood Pressure Management Before, During, and After Endovascular Thrombectomy for Acute Ischemic Stroke - de Havenon, Adam; Petersen, Nils; Sultan-Qurraie, Ali; Alexander, Matthew; Yaghi, Shadi; Park, Min; Grandhi, Ramesh; Mistry, Eva (Seminars in Neurology, 2021)
There is an absence of specific evidence or guideline recommendations on blood pressure management for large vessel occlusion stroke patients. Until randomized data are available, the periprocedural blood pressure management of patients undergoing endovascular thrombectomy can be viewed in two phases relative to the achievement of recanalization. In the hyperacute phase, prior to recanalization, hypotension should be avoided to maintain adequate penumbral perfusion. The American Heart Association guidelines should be followed for the upper end of prethrombectomy blood pressure: ≤185/110 mm Hg, unless post–tissue plasminogen activator administration when the goal is <180/105 mm Hg. After successful recanalization (thrombolysis in cerebral infarction [TICI]: 2b–3), we recommend a target of a maximum systolic blood pressure of < 160 mm Hg, while the persistently occluded patients (TICI < 2b) may require more permissive goals up to <180/105 mm Hg. Future research should focus on generating randomized data on optimal blood pressure management both before and after endovascular thrombectomy, to optimize patient outcomes for these divergent clinical scenarios.
Keywords: blood pressure; acute ischemic stroke; large vessel occlusion